THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (EWOM), PRODUCT QUALITY, AND PRICE TOWARDS PURCHASE INTENTION ON VIRGIN COCONUT OIL PRODUCT AT CV. EMKA INDOCOCO SEJAHTERA - Wowor, Gizell Natalie; Tumbuan, Willem J. F. A.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
As a local MSME in North Sulawesi, CV. Emka Indococo Sejahtera seeks to expand its market through digital platforms and product innovation. This study aims to examine the influence of Electronic Word of Mouth (eWOM), product quality, and price on consumer purchase intention for Virgin Coconut Oil (VCO) products in CV. Emka Indococo Sejahtera. This study uses a quantitative approach with an associative method, using a sample of 100 respondents selected from followers of Indococo's Instagram account. Data were collected through questionnaires and analyzed using multiple linear regression. The findings show that eWOM, product quality, and price significantly influence purchase intent both partially and concurrently. Among these factors, eWOM has the strongest effect on purchase intent. These results demonstrate the importance of building positive digital communication, maintaining product quality, and offering competitive pricing strategies to improve consumer interest and purchasing behavior. The research contributes to the development of local MSME marketing strategies in the digital era.   Keywords: Electronic Word of Mouth, Product Quality, Price, Purchase Intention, Virgin Coconut Oil